(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
A virtual CAD system for thermal functional design is reported in this paper. An improved multi-style garment design and segmental condition specification was achieved in this system. Moreover, this system predicted the thermal status of human and clothing system while the predicted results correspond well with the experimental results. Both 3D static and dynamic visualization were presented to the users to get a feedback for the design case.